Presenting a Stochastic Model of Simultaneous Planning Problem of Distribution and Subtransmission Network Development considering the Reliability and Security Indicators - Seyed Hossein Moayed; Hosein Hasan Shahi; Mohammadreza Akbarizadeh; Morteza Jadidoleslam; Arash Aghatehrani; Afshin Pirouzi (International Transactions on Electrical Energy Systems)
Consumption growth demands power system expansion, and changes in a network lead to changes in operation indices of the upstream network. Hence, to establish a reliable planning of the distribution network, simultaneous planning of the subtransmission network should also be taken into account. It is predicted that this planning impacts different technical indices; therefore, formulation of various technical indices need to be included in the planning model. Therefore, in this study, the stochastic problem model of simultaneous planning of distribution and super distribution network development considering the reliability and security indicators is presented. The aforementioned problem is in the form of an optimization problem whose objective function is to minimize the costs of construction, replacement, operation, maintenance, reliability, and security. Furthermore, the mentioned problem is bound to the equations of power distribution, reliability, and security of voltage in addition to the limitation of network indicators. It is worth mentioning that, in the proposed problem, the active and reactive loads in addition to the operating price are in the form of uncertainty. Thus, the mentioned problem is in the form of a stochastic problem in which the point estimation method is used to evaluate the scenarios. Simultaneous expansion planning of distribution and subtransmission networks along with the placement of distributed generations and capacitors, as well as modeling security and reliability indices, is the novelty of the proposed scheme. In the end, the proposed problem is applied to the test network by GAMS optimization software, and then the capabilities of the proposed problem are extracted. Accordingly, based on numerical results, the expansion of distribution networks imposes considerable cost. Moreover, expansion planning of both distribution and subtransmission networks helps voltage to be in its permissible range, lower power loss, and improve reliability and security to 100%.